2021
DOI: 10.1002/ecy.3465
|View full text |Cite
|
Sign up to set email alerts
|

Plant traits and soil fertility mediate productivity losses under extreme drought in C3 grasslands

Abstract: Extreme drought decreases aboveground net primary production (ANPP) in most grasslands, but the magnitude of ANPP reductions varies especially in C3‐dominated grasslands. Because the mechanisms underlying such differential ecosystem responses to drought are not well resolved, we experimentally imposed an extreme 4‐yr drought (2015–2018) in two C3 grasslands that differed in aridity. These sites had similar annual precipitation and dominant grass species (Leymus chinensis) but different annual temperatures and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 35 publications
12
55
0
Order By: Relevance
“…Plant height is a trait associated with plant growth ability, so community productivity usually increases with plant height (Moles et al, 2009 ; Luo et al, 2021 ). However, in our study area, winds are strong in the growing season, and gales above force 7 are frequent and occur for over 80 days annually, which leads to plants widespread dwarfing (Zhang et al, 2013 ; Xu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant height is a trait associated with plant growth ability, so community productivity usually increases with plant height (Moles et al, 2009 ; Luo et al, 2021 ). However, in our study area, winds are strong in the growing season, and gales above force 7 are frequent and occur for over 80 days annually, which leads to plants widespread dwarfing (Zhang et al, 2013 ; Xu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism governing the impact of precipitation and N content on ANPP is not yet well-understood (Weltzin et al, 2003 ; Ogle and Reynolds, 2004 ; Luo et al, 2021 ; Guo et al, 2022 ). Generally, the changes in precipitation determine the changes in ANPP by triggering physiological responses of individual plants and based on community attributes (plant density, height, species richness, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The paths of SEMs were modified according to p values of Fisher's C statistic and AIC (Luo et al, 2021). The stability of nondominant functional groups was not considered in the SEM, as it did not effectively improve the fit of the model.…”
Section: Methodsmentioning
confidence: 99%
“…The piecewiseSEMs were constructed based on a priori knowledge from the literature (Zhou et al, 2019) and the causal relationships found in multiple regression (Table 2) and correlation analysis (Figure ) of effects on community biomass stability. The paths of SEMs were modified according to p values of Fisher's C statistic and AIC (Luo et al, 2021). The stability of nondominant functional groups was not considered in the SEM, as it did not effectively improve the fit of the model.…”
Section: Methodsmentioning
confidence: 99%
“…According to the land use in the LHRB, grasslands and cultivated lands are the main land use types in the north. Previous studies reported that drought would lead to plant trait losses [70], and drought conditions are severe in the north LHRB [71]. Thus, it is possible that the drought in the north LHRB causes the EQ of grasslands and cultivated lands to be as low as that of construction lands (Figure 9).…”
Section: Trend Analysis Of Ecological Qualitymentioning
confidence: 96%